AI Integration in Nigeria’s Financial Sector: Challenges and Opportunities for Professional Development - Muhammad, Adamu Abubakar; Ardo, Adam Muhammad; Aliyu, Shafa'at Ahmad; Muhammad, Ibrahim Abubakar; Jika, Fadimatu Ahmed (IDRIS Darulfunun Institute, 2025)
Artificial Intelligence (AI) is transforming banking, accounting, auditing, risk management, and customer service operations. In Nigeria, the integration of AI into the financial sector presents both unprecedented opportunities and significant challenges. This study examines the implications of AI adoption for professional development among Nigerian finance practitioners. Based on the frameworks of technological diffusion and human capital development, the research investigates how AI-driven tools like machine learning, natural language processing, robotic process automation, and predictive analytics are influencing financial practices and the skills required of professionals. The study uses a mixed-methods approach, combining survey data from finance professionals in selected Nigerian banks and fintech firms with qualitative interviews with regulators, educators, and technology experts. In addition to highlighting important opportunities like increased productivity, fraud detection, financial inclusion, and better decision-making, the findings are anticipated to point out significant obstacles like job displacement, ethical dilemmas, regulatory gaps, and a lack of professional AI literacy. In order to create a workforce prepared for AI, the study emphasizes the necessity of ongoing professional development, curriculum change in finance and accounting education, and cooperative efforts between the government, business community, and professional associations. The study conclude that effective AI integration in Nigeria's financial sector depends not only on the availability of technology but also on giving finance professionals the knowledge, moral compass, and flexible abilities they need to prosper in the age of digital transformation.